Prepaid RFID-based Electricity Payment System for Rooming Houses - Sitompul, Erwin; Syirli, Khoerrudin (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2020)
A prepaid RFID-based electricity payment system is proposed in this paper. The system is intended for rooming houses where residents’ electricity overconsumption and outstanding payment are to be avoided by the house owner. An RFID-card is used as the payment instrument. The system consists of two units, the card balance top-up unit (CTU) and the energy credit top-up unit (ETU). The balance of the RFID-card is topped up by using the CTU. With the balance stored in it, the RFID-card is to be used to top-up the energy credit at the ETU. Each of the CTU and the ETU is equipped with a microcontroller, an RFID reader/writer and a user interface in the form of keypad and liquid crystal display (LCD). Furthermore, the ETU utilizes a relay to control the flow of electricity. If the energy credit of a room is exhausted, then the supply of electricity to the room is cut off by the relay. The electricity consumption is calculated based on the number of pulses of the calibration LED of a standardized electronic energy meter. The pulse is transmitted to the microcontroller by using an optocoupler. The RFID-card records the current card balance, the card’s top-up history, and the card’s usage history. The energy credit is stored in the EEPROM of the ETU’s microcontroller. The energy meter is tested to measure the energy consumption of two loads based on the pulses of its calibration LED. The actual power of the two loads are 87.25 % and 94.23 % of the corresponding power rating. The card balance top-up process at the CTU and the energy credit top-up process at the ETU are successfully checked. After every balance top-up and credit top-up, the current card balance is calculated and stored correctly. During the electricity usage, the LCD of the ETU shows the remaining energy credit in IDR and kWh. These are accumulatively reduced every time the pulse count reaches a certain reset number, which corresponds to the electrical energy’s unit price applied. The proposed electricity payment system can be a solution for owners of rooming houses to secure electricity payments from the residents. The installation cost of the system is low and without the need to change the existing electricity purchase method of the house. The house owner also can individually adjust the maximum power limit for each room.